2011
DOI: 10.1111/j.1365-2036.2011.04730.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: otilonium bromide improves frequency of abdominal pain, severity of distention and time to relapse in patients with irritable bowel syndrome

Abstract: SUMMARY Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 23 publications
3
99
0
7
Order By: Relevance
“…Another multicenter clinical trial also revealed that patients receiving otilonium bromide were less likely to present with symptom recurrence versus placebo (106).…”
Section: Efficacymentioning
confidence: 99%
“…Another multicenter clinical trial also revealed that patients receiving otilonium bromide were less likely to present with symptom recurrence versus placebo (106).…”
Section: Efficacymentioning
confidence: 99%
“…Therefore, this class of agents can counteract three mechanisms that contribute to chronic diarrhea. Clinical trials show greatest effect of otilonium on abdominal sensation rather than bowel dysfunction in patients with IBS (47,48). A small trial using crossover design showed similar efficacy of solifenacin and ramosetron (49).…”
Section: Chronic Diarrheamentioning
confidence: 99%
“…A randomised, double-blind clinical trial demonstrated a lower rate of symptom relapse (P=0.009) and higher relapse-free probability (P=0.038) in patients treated with otilonium bromide for 15 weeks compared with patients treated with placebo. 34 A 2-year study demonstrated a significant improvement in abdominal pain, abdominal distension, and bowel movements in patients treated with otilonium bromide, compared with a high-roughage diet. 35 Statement 19: Antispasmodics are also commonly prescribed in combination with antidiarrhoeal drugs or laxatives.…”
Section: Rome III Rome Ivmentioning
confidence: 99%
“…Nearly all were mild to moderate (99% in the otilonium bromide group and 98% in the placebo group) and were considered unrelated to the study treatment (92% in the otilonium bromide group and 94% in the placebo group). 34 Statement 18: Further study is warranted to establish an optimal treatment period for otilonium bromide.…”
Section: Rome III Rome Ivmentioning
confidence: 99%